The influence of professional investors on the failure of management buyout attempts - Peck, Sarah W. (Journal of Financial Economics, 1996)
In a sample of 111 MBO offers between 1984 and 1987, almost 30% attract new blockholders. These blockholders are primarily professional investors who act to facilitate a takeover by a higher bidder, thus increasing returns to both themselves and other public shareholders. In contrast, I find little evidence that pre-existing blockholders, particularly institutional holders, affect either the offer outcome or actively participate in the buyout contest once it begins. The overall pattern of results suggests that professional investors, particularly equity-holding companies, are ‘control specialists’ who provide valuable services as brokers in the market for corporate control.